Beliefs about health and illness and health-related behavior among urban women with gestational diabetes mellitus in the south east of China. (November 2016) - Ge, Li; Albin, Björn; Hadziabdic, Emina; Hjelm, Katarina; Rask, Mikael
Purpose: The incidence of gestational diabetes among Chinese women is 4.3%. No study has previously been conducted about beliefs and health-related behavior among urban Chinese women with this disease. This article aims to explore beliefs about health and illness and health-related behavior among women in this group in a Chinese sociocultural context.Design: A qualitative exploratory study was conducted and semistructured individual interviews ( n = 15) were processed by content analysis.Results: Beliefs about health and illness among these women were foremost attributed to the individual, social, and natural worlds. They feared the negative influence of gestational diabetes, but some of them believed in "letting nature take its course" and "living in the present." Their care-seeking behavior varied between the professional, popular, and folk sectors. They sought a balance between following professionals' advice and avoiding practical difficulties.Conclusion: The beliefs and health-related behavior among them were influenced by Chinese culture, which can sometimes but not always reduce the effect of the disease.